Cognitive decline in an adult with ATR-16 syndrome due to an unbalanced translocation between 11p15.5 and 16p13.3: a case report - Krutish, Angela; Kukurudz-Gorowski, Rebekah; Borlot, Felippe; Frosk, Patrick; Rockman-Greenberg, Cheryl; Mhanni, Aizeddin A. (Frontiers in Genetics, 2025)
BackgroundChromosome 16p13.3 deletions cause a contiguous gene deletion syndrome, ATR-16 syndrome. The classic phenotype of ATR-16 syndrome includes either alpha-thalassemia trait or hemoglobin H disease and intellectual disability; however, considerable variable expressivity has been reported with some patients having only an alpha-thalassemia disorder and others exhibiting a more severe phenotype with additional features.Case presentationWe describe an adult male with ATR-16 syndrome (due to an unbalanced de novo translocation involving chromosomes 11p15.5 and 16p13.3) who developed cognitive decline and increasing dyskinetic movements in his late twenties. Biochemical investigations and exome sequencing did not elucidate an alternative explanation for this decline. Furthermore, neither the deletion on chromosome 16 nor the duplication on chromosome 11 encompassed genes that could explain the decline.ConclusionWhile cognitive decline has not been previously reported in ATR-16 syndrome, this may be another feature of the condition that is subject to variable expressivity. Taking this together with the apparent increased prevalence of dementia in other neurodevelopmental conditions, we hypothesize that individuals with ATR-16 syndrome may be predisposed to early cognitive decline.